Desempeño hidráulico del sistema de riego por aspersión comunidad Sanjapamba: Mediante modelo matemático - Estrada Bulla, Andrés Fernando (2024)
Sprinkler irrigation systems are one of the most effective technologies for distributing water uniformly to crops. But, there are certain problems between theoretical design and their actual performance in the field. Despite the technical specifications and design calculations, many systems face difficulties to meet the adequate performance for water distribution. For this reason, the present study aims to evaluate the performance of the sprinkler irrigation system in the community of Sanjapamba, San Andres, determining its hydraulic behavior and performance. For this purpose, a mathematical model was developed to compare the current performance of the system with its original design, identifying differences, trends or significant relationships. The research follows a mixed methodological approach, combining quantitative and qualitative aspects. In the quantitative part, the collection and analysis of hydraulic data was carried out, using the EPANET mathematical model to simulate the behavior of the irrigation system. This simulation allows the evaluation of parameters such as pressure, velocity and flow rate. In the qualitative part, field visits provided information on the operations, condition and maintenance of the system, including in situ pressure measurements and gauging. Finally, the results reveal that the actual system exceeds the parameters established in the original design at certain points, particularly in specific sprinklers, where higher values in velocity, flow and pressure are recorded. This deviation recommends the need for operational adjustments to optimize the hydraulic efficiency of the system, ensuring operation more in line with design requirements and efficient use of resources.